2017
DOI: 10.1016/s0016-5085(17)30692-3
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Use is Associated with Lower Risk of Barrett's Esophagus in Women

Abstract: OBJECTIVES: Barrett's esophagus (BE) is the only known precursor to esophageal adenocarcinoma. Data examining the association of aspirin with the onset of BE, particularly for women, are scant and conflicting. METHODS: We leveraged data from 121,700 women enrolled in the Nurses' Health Study, a large prospective cohort study, who biennially provided detailed information regarding endoscopy and use of aspirin. We used unconditional logistic regression to obtain multivariable (MV)-adjusted odds ratios (ORs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(96 reference statements)
0
3
0
Order By: Relevance
“… 14 Esomeprazole is the most commonly used PPI in the USA, and allows the healing of oesophagitis without promoting clonal expansion of Barrett's oesophagus. 15 Observational data suggest that aspirin use is associated with reduced risk of oesophageal adenocarcinoma, 16 , 17 , 18 , 19 but this is not a universal finding. 20 Finally, although Barrett's oesophagus is a major risk factor for oesophageal adenocarcinoma, only a minority of patients with Barrett's oesophagus die from oesophageal adenocarcinoma; most die from cardiovascular disease or chest infections.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Esomeprazole is the most commonly used PPI in the USA, and allows the healing of oesophagitis without promoting clonal expansion of Barrett's oesophagus. 15 Observational data suggest that aspirin use is associated with reduced risk of oesophageal adenocarcinoma, 16 , 17 , 18 , 19 but this is not a universal finding. 20 Finally, although Barrett's oesophagus is a major risk factor for oesophageal adenocarcinoma, only a minority of patients with Barrett's oesophagus die from oesophageal adenocarcinoma; most die from cardiovascular disease or chest infections.…”
Section: Introductionmentioning
confidence: 99%
“…However, data from this randomized controlled trial supports previous observational data which suggested a chemopreventive link between EAC aspirin and PPI, and metanalysis data from cardiovascular studies with aspirin which showed lower EAC rates (though these were not primary end points). 96,97 The way in which the AspECT data is interpreted may be similar to the other recommendations discussed in this paper -targeting of high -risk groups to streamline interventions is likely to be the future.…”
Section: Barrett Esophagus and The Benign Barrett's And Can-mentioning
confidence: 64%
“…In the Nurses’ Health study, 667 patients developed BE among 27,881 women over 18 years of follow-up. 28 Using multivariate analysis, women who regularly used aspirin had a lower risk of BE (OR = 0.85; CI = 0.72–0.99). Similar results were demonstrated in a case-control study where patients on regular aspirin had lower risk of BE especially among persons with GERD symptoms.…”
Section: Evidence For Prevention Of Be In General Populationmentioning
confidence: 99%